Government Ownership and Value of Listed Firms in Kenya: A Panel Data Evidence - Odhiambo, Fredrick Onyango; Omindi, Nixon Oduor (American Journal of Trade and Policy, 2015)
This study examines the relationship between government ownership and performance of listed firms on the Nairobi Securities Exchange. The quadratic term of government ownership is included in the model to test for the effect of increasing government ownership levels on performance. We use panel data techniques on 102 firm-year observations between 2003 and 2013 for all the listed firms in which the government directly owns some shares. We find no relationship between government ownership and performance at lower levels of government ownership. We find a negative relationship between government ownership and performance at higher levels of government ownership. We estimate, through differentiation of the Tobin’s Q model, that government ownership has a negative effect on performance when government ownership exceeds 41%. The study concludes that lower government ownership levels do not affect firm performance but as the ownership rises, government ownership has a detrimental effect on firm performance. We provide implications of these results for policy and practice.JEL Classifications Code: G34
Keywords: Government Ownership; Performance; Nairobi Securities Exchange; Panel Data